Understanding gender differences in students’ anxiety in a seminar presentation - Suardi Sahid; Aldiansyah; Iskandar (Center for Humanities and Innovation Studies, 2018)
This paper discusses students` anxiety and gender differences faced by male and female in the presentation. The main focus is to see the anxiety affected by gender differences in a presentation at the State University of Makassar conducted in 2016, the subjects of this research were the students` at Graduate Program who conduct seminar presentation from September to the last of December. The researcher used purposive sampling by taking two males and two female students as a participant to be observed. The instruments that the researcher used were Observation checklist, field notes, and interview. The result of the research shows the significance related anxiety and gender differences which male anxiety is affected by their thought while female anxiety is affected by their feeling in a seminar presentation.